S139 The role of endothelin receptors (ETRA/B) in fibrocyte differentiation. (14th November 2013) - Trinder, SLl; Shi-wen, X; Ahmed Abdi, B; Denton, CP; Budd, DC; Abraham, DJ; Holmes, AM
Abstract : Introduction: Scleroderma (SSc) is an autoimmune connective tissue disease of unknown aetiology. Pulmonary involvement including the development of pulmonary arterial hypertension (PAH) is characterised by vascular remodelling, collagen deposition and expression of connective tissue growth factor (CTGF). CD14 + monocytes can differentiate into spindle shaped cells termed 'fibrocytes'. Fibrocytes express haematopoietic and mesenchymal markers including collagen, and amplify inflammatory/immune responses via antigen presentation and chemokine secretion. Fibrocyte differentiation is enhanced by fibrogenic cytokines including PDGF. The role fibrocytes play in promoting PAH in SSc is unknown. Methods: CD14 + PBMCs were isolated from SSc and healthy donor blood. Fibrocyte differentiation in the presence of MCSF and/or ET-1 was assessed after 14 days. The effect of endothelin receptor (ETR) antagonists (selective/dual) on fibrocyte differentiation (n = 6) was investigated. SSc and control fibrocyte secretomes were assessed by ELISA (n = 6), and the effects on fibroblast-mediated gel contraction determined. Results: MCSF and ET-1 alone and in combination induced fibrocyte differentiation (P < 0.05). SSc fibrocytes exhibited enhanced differentiation from CD14 + PBMCs than healthy control donors in response to MCSF (P < 0.05), ET-1 (P < 0.05) and in combination (P < 0.01). ETR antagonists BQ123 (ETRA ), BQ788 (ETRB ) and Bosentan (ETRA/B ) inhibited MCSF induced fibrocyte differentiation. CTGF secretion was elevated in SSc compared to control fibrocytes (P < 0.05) cultured with MCSF. Conditioned media from SSc fibrocytes promoted gel contraction by control pulmonary fibroblasts (P < 0.05). Discussion: CD14 + SSc PBMCs readily differentiate into fibrocytes in response to ET-1 and MCSF via ETRA and ETRB . Our data suggests fibrocytes contribute to the development of PAH in SSc via a paracrine mechanism modulating the functional activities of resident tissue fibroblasts.